The Objective of this Study is to Examine the Relationship Between Work Experience, Age and the Quality of Nurse Jobs - Zaenal; Dwi Esti Handayani; Much. Asdi (CV. Get Press Indonesia, 2024)
The nursing profession is a crucial component of the healthcare system, providing direct care to patients, supporting the healing process, and improving patients' quality of life. The quality of nurses' work, which includes clinical, communication, and care management skills, greatly influences patient care outcomes and overall health system efficiency (Supitra & Kusumawardhani, 2023). This study aims to explore and analyse the relationship between work experience, age, and nurses' work quality in context. This research will use a quantitative approach with a correlational study research design. The population is all nurses working in a hospital with the sample will be drawn by stratified random sampling to ensure good representation of different levels of experience and age. The data showed that the majority of respondents had more than 5 years of work experience (68.4%), most respondents were in the age range of 26-35 years (61.4%), the distribution of nurses' work quality showed that most nurses were considered to have good work quality (52.6%). The relationship between work experience and work quality p-value of 0.007 indicates that the relationship between work experience and nurse work quality is statistically significant. The relationship between age and work quality p-value of 0.001 indicates that the relationship between age and work quality of nurses is also statistically significant. It is necessary to develop continuous training and career development programmes to improve nurses' skills and competencies, especially for those with less than 5 years of work experience.